DOMINANT NEGATIVE MUTANTS OF TRANSDUCIN-α THAT BLOCK ACTIVATED RECEPTOR - Natochin, Michael (2006)
Mutations counterpart to dominant negative RasSer17Asn in the α-subunits of heterotrimeric G-proteins are known to also produce dominant negative effects. The mechanism of these mutations remains poorly understood. Here, we examined the effects and mechanism of the Ser43Cys and Ser43Asn mutants of transducin-like chimeric Gtα* in the visual signaling system. Our analysis showed that both mutants have reduced affinity for GDP and are likely to exist in an empty- or partially occupied-pocket state. S43C and S43N retained the ability to interact with Gtβγ and, as heterotrimeric proteins, bind to photoexcited rhodopsin (R*). The interaction with R* is unproductive as the mutants failed to bind GTPγS and become activated. S43C and S43N inhibited R*-dependent activation of Gtα* and Gtα, apparently by blocking R*. Finally, both Gtα* mutants lacked interaction with the γ-subunit of PDE6, an effector protein in phototransduction. These results indicate that the S43C and S43N mutants of Gtα* are dominant negative inhibitors that bind and block the activated receptor in a mechanism that parallels that of RasSer17Asn. Dominant negative mutants of Gtα sequestering R*, such as S43C and S43N, may become useful instruments in probing the mechanisms of visual dysfunctions caused by abnormal phototransduction signaling.